Analisis Daya Dukung–Daya Tampung Air Dan Implikasinya Terhadap Pengelolaan Ruang Di Kelurahan Sukarame Kota Bandar Lampung - Hevi Fatia; Fachri Muhammad Rasyid; Baiq Rindang Aprildahani (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
sustainable spatial planning. Rapid urban development in Sukarame Village has the potential to reduce the environment’s capacity to provide water, while water demand continues to increase due to population growth. This study aims to analyze water carrying capacity, water demand capacity, the relationship between water availability and water demand, and their implications for spatial planning in Sukarame Village, Bandar Lampung City. A descriptive quantitative approach combined with spatial analysis using a 150 × 150 m grid system was employed in this study. Water carrying capacity was assessed using the Environmental Services Index (ESI) for Water Provision, while water demand capacity was estimated by calculating domestic water demand based on population distribution. The results indicate that the total water availability in Sukarame Village is 921,212.28 m³/year, whereas domestic water demand reaches 1,934,602.31 m³/year, resulting in a water deficit of 1,013,390.03 m³/year. These findings indicate that the existing water carrying capacity is insufficient to meet the community's water demand, demonstrating that the balance between water carrying capacity and water demand capacity has been exceeded. The water deficit is primarily influenced by the dominance of built-up areas, which reduces groundwater recharge areas and increases pressure on water resources. The findings suggest that assessments of water carrying capacity and water demand capacity can serve as an important basis for spatial planning policies, particularly in controlling land-use conversion, protecting groundwater recharge areas, and increasing green open spaces to support the sustainable management of water resources.